2002
DOI: 10.1002/ajmg.10183
|View full text |Cite
|
Sign up to set email alerts
|

Full genome screen for Alzheimer disease: Stage II analysis*

Abstract: We performed a two-stage genome screen to search for novel risk factors for late-onset Alzheimer disease (AD). The first stage involved genotyping 292 affected sibling pairs using 237 markers spaced at approximately 20 cM intervals throughout the genome. In the second stage, we genotyped 451 affected sibling pairs (ASPs) with an additional 91 markers, in the 16 regions where the multipoint LOD score was greater than 1 in stage I. Ten regions maintained LOD scores in excess of 1 in stage II, on chromosomes 1 (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
171
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(189 citation statements)
references
References 33 publications
(50 reference statements)
15
171
3
Order By: Relevance
“…A fact consistent with this observation is that genome-wide screens have identified several regions that show significant linkage to AD, of which the most likely to harbor new risk factors are chromosomes 1, 9, 10, 12, 19 and 21 (Pericak-Vance et al, 1997;Rogaeva et al, 1998;Wu et al, 1998;Kehoe et al, 1999;Scott et al, 2000;Mayeux et al, 2002;Myers et al, 2002;Blacker et al, 2003;Saunders et al, 2003). Several candidate gene association studies have recently focused in examining common genetic variation among Wnt signaling components in AD.…”
Section: Alzheimer's Disease Apolipoprotein E and Wnt Signalingmentioning
confidence: 76%
“…A fact consistent with this observation is that genome-wide screens have identified several regions that show significant linkage to AD, of which the most likely to harbor new risk factors are chromosomes 1, 9, 10, 12, 19 and 21 (Pericak-Vance et al, 1997;Rogaeva et al, 1998;Wu et al, 1998;Kehoe et al, 1999;Scott et al, 2000;Mayeux et al, 2002;Myers et al, 2002;Blacker et al, 2003;Saunders et al, 2003). Several candidate gene association studies have recently focused in examining common genetic variation among Wnt signaling components in AD.…”
Section: Alzheimer's Disease Apolipoprotein E and Wnt Signalingmentioning
confidence: 76%
“…Linkage studies have identified several promising chromosomal regions to harbor additional AD genes, including chromosomes 12, 10, 9 and 6 [reviewed in 7]. A broad linkage peak encompassing >60 cM region between chromosome 10q21 and 10q25 that influence both AD risk and AAO has been suggested [2,4,10,13]. There are more than 300 genes in this broad genomic region of chromosome 10 and thus the task of identifying the chromosome 10 candidate gene is daunting.…”
Section: Introductionmentioning
confidence: 99%
“…Loci likely to contain any gene of interest for AD have been defined using bibliographic study, [6][7][8][9] based on the analysis of previously published genome scan results obtained from late-onset familial forms of AD (Table 1).…”
Section: Selection Of Regions Of Interestmentioning
confidence: 99%
“…We planned to make home-made microarrays to screen all ORFs contained in the risk-associated loci (over nine different chromosomes) previously identified in genome scan studies. [6][7][8][9] Two approaches were defined: (i) the first one is based on the development of specific PCR probes from a bank of 12 000 unique cDNAs; (ii) the second one consists in developing specific oligonucleotides. The aim of this report was to show the relevance and limitations of the bio-informatics analysis work, which we developed from NCBI database, to select ORFs of interest for this project.…”
Section: Introductionmentioning
confidence: 99%